2014
DOI: 10.1016/j.foodchem.2013.10.086
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of the extraction of phenolic compounds from apples using response surface methodology

Abstract: The extraction of phenolic compounds from apples was optimised using response surface methodology (RSM). A Box-Behnken design was conducted to analyse the effects of solvent concentration (methanol or acetone), temperature and time on the extraction of total phenolic content, total flavonoids and antioxidant capacity (FRAP and DPPH). Analysis of the individual phenolics was performed by HPLC in optimal extraction conditions. The optimisation suggested that extraction with 84.5% methanol for 15 min, at 28 °C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(107 citation statements)
references
References 24 publications
8
94
1
4
Order By: Relevance
“…As well as PCA, initially all variables were autoscaled and the models were built. The statistical significance of the equations was examined by ANOVA and goodness-of-fit was evaluated based on the regression coefficients (R 2 ), adjusted R 2 , accuracy factor (AF), and bias factor (BF) (Alberti et al 2014;Patras et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…As well as PCA, initially all variables were autoscaled and the models were built. The statistical significance of the equations was examined by ANOVA and goodness-of-fit was evaluated based on the regression coefficients (R 2 ), adjusted R 2 , accuracy factor (AF), and bias factor (BF) (Alberti et al 2014;Patras et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…These preliminary temperatures were set with respect to the lowest and highest temperatures that could produce adequate precision by UAE system. A binary solvent of methanol: water was chosen as this normally used for the extraction of phenolics from foods [12][13][14].…”
Section: Phenolic Recoveries Exposed By Different Uae Temperaturementioning
confidence: 99%
“…Their ultraviolet (UV) spectra correspond to phenolic families analyzed as flavan-3-ol and dihydrochalcone (280 nm), hydrocinnamic acid (320 nm) and flavonol (350 nm). 32 Farhadi et al 22 studied different cultivars, species and parts of grapes (seed, skin, peel and pulp) and identified other compounds with antioxidant capacities beyond those found in this work, particularly catechin, epicatechin, quercetin and rutin flavonoids. Tournour et al 8 conducted comparative studies of different varieties of Portuguese grapes using different methods of extraction, and their studies have revealed the presence of gallic acid, caffeic acid, syringic acid, catechin and epicatechin, and the major compounds were syringic acid and catechin.…”
Section: Resultsmentioning
confidence: 56%